Pancasila and Religious Values in Establishment of Legal Regulations - Hoiru Nail, Muhammad; Utama, Made Arya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 2 (2020), 2020)
In the news today (news update), Indonesia was briefly chopped off with headlines from the religion of the great enemy Pancasila. In this paper, we will discuss the relationship between Pancasila, religion and the formation of legislation. This is deliberately discussed in this paper to avoid greater mistakes especially for Indonesian people related to the relationship of religious values ??and Pancasila, as well as the relationship of religious values ??with the Formation of Laws and Regulations. This research is qualified into normative legal research that starts from the obscurity of the norms, namely Article 2 the Formation of Laws and Regulations that stated "Pancasila, the source of all sources of state law". The results of this study indicate that religion and Pancasila are not contradicting. Pancasila is formed on the basis of noble values ??and virtues that exist in each religion which later becomes the first precepts of Pancasila "The Godhead of the One". The relationship of religious values ??with the formation of legislation is very thick when juridically the religion animates the opening of paragraph 3 of the 1945 Constitution of the Republic of Indonesia and several existing legal products are reflected/based on religion.